1986
DOI: 10.3146/i0095-3679-13-2-11
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Three Digging Dates on Oil Quality, Yield, and Grade of Five Peanut Genotypes Grown Without Leafspot Control1

Abstract: Five peanut (Arachis hypogaea L.) genotypes, Southern Runner, Dixie Runner, Florunner, UF82206, and UF714021, were grown for three years, 1982–1984, near Gainesville, Florida without fungicide applications. Three digging dates, averaging 105 days after planting (DAP), 118 DAP, and 132 DAP, were used each year to determine the effects of early harvest as a management practice for peanut production under leafspot pressure. The different digging dates had no effect on fatty acid composition of the five genotypes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
26
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 0 publications
14
26
0
Order By: Relevance
“…Peanuts harvested at 155 DAP had slightly lower oil content (48.2%) than those harvested at 125 DAP (50.8%). Rnauft et al (1986) reported that oil contents of Florunner peanuts harvested at 105 and 132 d were 48.9 and 46.7%, respectively (dry basis), comparable to the results of this study. Carbohydrates content decreased from 27.4% at 110 DAP to 25.1% at 115 DAP.…”
Section: Compositional Analysessupporting
confidence: 90%
“…Peanuts harvested at 155 DAP had slightly lower oil content (48.2%) than those harvested at 125 DAP (50.8%). Rnauft et al (1986) reported that oil contents of Florunner peanuts harvested at 105 and 132 d were 48.9 and 46.7%, respectively (dry basis), comparable to the results of this study. Carbohydrates content decreased from 27.4% at 110 DAP to 25.1% at 115 DAP.…”
Section: Compositional Analysessupporting
confidence: 90%
“…Knauft et al (2), also using one planting date and five genotypes harvested at three dates (105,118, and 132 days after planting), found that earlier digging dates tended to reduce market grade characters. In their study without leafspot control, major yield differences were the result ofgenotype x digging date interactions.…”
mentioning
confidence: 96%
“…Many pods remained in the soil when plant were dug and inverted at this time, so the decline may be due to pod loss. This corresponds with the observation by Knauft et al (16) where Florunner lost more than halfits pod yield when harvested at 132 versus 118 DAP. In their study, however, fungicides were not used to control the leafpot epidemics.…”
Section: -----mentioning
confidence: 82%
“…Many studies on peanut culture focus only on the endproducts ofyield and grade (7,16,17). Other researchers have examined growth characteristics of peanut to better understand energypartitioning (10) and provide information suitable for plant modeling efforts (5,33).…”
mentioning
confidence: 99%